2018
DOI: 10.1016/j.bbmt.2018.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ultrasonographic Scoring System of Sinusoidal Obstruction Syndrome after Hematopoietic Stem Cell Transplantation

Abstract: Sinusoidal obstruction syndrome (SOS)/hepatic veno-occlusive disease (VOD) is a well-documented complication after hematopoietic stem cell transplantation (HSCT). Transabdominal ultrasonography (US) enables the visualization of blood flow abnormalities and is therefore useful for the diagnosis of SOS/VOD. We herein prospectively evaluated accuracy of a novel US diagnostic scoring system of SOS/VOD based on US findings. We carried out US in 106 patients on day 14 and when SOS/VOD was suspected after allogeneic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 25 publications
(45 reference statements)
4
43
0
Order By: Relevance
“…Several studies have demonstrated early diagnosis or prediction of VOD/SOS with this method, before the appearance of conventional clinical criteria [74][75][76]. Other proposed methods involve the multifactorial, or panel, scoring approach for early diagnosis or prediction of VOD/SOS with the use of ultrasound [77][78][79][80]. Independent predictors of VOD/SOS that may enhance ultrasound diagnosis include gallbladder wall thickening and paraumbilical vein blood flow [78,80].…”
Section: New Diagnostic Techniques/parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated early diagnosis or prediction of VOD/SOS with this method, before the appearance of conventional clinical criteria [74][75][76]. Other proposed methods involve the multifactorial, or panel, scoring approach for early diagnosis or prediction of VOD/SOS with the use of ultrasound [77][78][79][80]. Independent predictors of VOD/SOS that may enhance ultrasound diagnosis include gallbladder wall thickening and paraumbilical vein blood flow [78,80].…”
Section: New Diagnostic Techniques/parametersmentioning
confidence: 99%
“…Other proposed methods involve the multifactorial, or panel, scoring approach for early diagnosis or prediction of VOD/SOS with the use of ultrasound [77][78][79][80]. Independent predictors of VOD/SOS that may enhance ultrasound diagnosis include gallbladder wall thickening and paraumbilical vein blood flow [78,80]. Proposed methods aimed at diagnosis or prediction specifically of chemotherapy-induced VOD/SOS include a score consisting of expression of CD34 cells, increased levels of smooth muscle actin, and aberrant expression of glutamine synthetase [79].…”
Section: New Diagnostic Techniques/parametersmentioning
confidence: 99%
“…VOD/SOS is commonly characterized by hepatomegaly or right upper-quadrant pain, ascites, weight gain, and hyperbilirubinemia [7,8]. Traditionally, the Baltimore or modified Seattle criteria have been used to diagnose VOD/SOS [8][9][10][11][12]. Use of the Baltimore criteria requires the presence of Biology of Blood and Marrow Transplantation journal homepage : www.bbmt.org hyperbilirubinemia (bilirubin 2 mg/dL) for diagnosis, whereas use of the modified Seattle criteria hyperbilirubinemia does not.…”
Section: Introductionmentioning
confidence: 99%
“…The European Society for Blood and Marrow Transplantation (EBMT) has also proposed a revised differential diagnostic criteria for both children and adults (Mohty et al , 2016; Corbacioglu et al , 2018). We have elected to streamline both current and past diagnostic criteria in one contemporary and versatile definition that incorporates more signs and symptoms as well as advances in the diagnostic procedures, including liver ultrasonography and Doppler studies, with the primary goal of increasing awareness of this haematological disease and thereby allowing for earlier detection and more rapid institution of therapy to improve survival (Herbetko et al , 1992; Teefey et al , 1995; Sharafuddin et al , 1997; Nishida et al , 2018). We propose the following revised SOS/VOD diagnostic criteria, which include two of the following criteria following HCT probably or directly secondary to VOD/SOS and not secondary to other aetiologies: elevated bilirubin (≥2 mg/l) (≥34·2 micromoles/l or upper institutional limits), unexpected weight gain, excessive (≥5% compared to baseline weight pre‐HCT) platelet transfusions consistent with refractory thrombocytopenia post‐HCT size, hepatomegaly for age or increased liver size compared to pre‐HCT, right upper quadrant pain (which may be difficult to assess in infants and small children), ascites confirmed by physical exam and/or imaging studies and/or reversal of portal venous flow (hepatofugal flow) by Doppler ultrasound of the liver (which may be a late finding).…”
Section: New Revised Diagnostic Criteria Of Sos/vodmentioning
confidence: 99%
“…The role of ultrasound in making the diagnosis and following disease progression has been investigated in several studies (Herbetko et al , 1992; Teefey et al , 1995; Sharafuddin et al , 1997; Nishida et al , 2018; Reddivalla et al , 2018). Most abnormalities noted on ultrasonography often serve to confirm clinical findings of SOS/VOD, particularly those which may be challenging to assess in overweight or young HCT recipients, and may assist in ruling out other entities included in the differential diagnoses.…”
Section: The Role Of Ultrasoundmentioning
confidence: 99%